2020
DOI: 10.1371/journal.pcbi.1007999
|View full text |Cite
|
Sign up to set email alerts
|

Locally adaptive Bayesian birth-death model successfully detects slow and rapid rate shifts

Abstract: Birth-death processes have given biologists a model-based framework to answer questions about changes in the birth and death rates of lineages in a phylogenetic tree. Therefore birth-death models are central to macroevolutionary as well as phylodynamic analyses. Early approaches to studying temporal variation in birth and death rates using birth-death models faced difficulties due to the restrictive choices of birth and death rate curves through time. Sufficiently flexible time-varying birth-death models are s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 35 publications
(64 citation statements)
references
References 65 publications
0
57
0
Order By: Relevance
“…The support of the uncorrelated model over the two autocorrelated models (GMRF and HSRMF), although the autocorrelated models were favored when using time-varying diversification rates without environmental variables (Fig. S7), could stem from the use of vague prior distribution which allows for more rate variation in autocorrelated models 21 . However, regardless of the specific environmentally-dependent diversification model, we inferred a negative correlation between diversification rates and environmental CO 2 (Fig.…”
Section: The Respective Diversification Rates Of Asteraceae and Poaceae (Calibration Scenario #1 See Methods) Peak Between 20mentioning
confidence: 99%
See 1 more Smart Citation
“…The support of the uncorrelated model over the two autocorrelated models (GMRF and HSRMF), although the autocorrelated models were favored when using time-varying diversification rates without environmental variables (Fig. S7), could stem from the use of vague prior distribution which allows for more rate variation in autocorrelated models 21 . However, regardless of the specific environmentally-dependent diversification model, we inferred a negative correlation between diversification rates and environmental CO 2 (Fig.…”
Section: The Respective Diversification Rates Of Asteraceae and Poaceae (Calibration Scenario #1 See Methods) Peak Between 20mentioning
confidence: 99%
“…We develop a novel Bayesian approach for detecting diversification-rate shifts that incorporates a more realistic (non-uniform) model of species sampling and implemented it in the open-source software RevBayes 17 . Our model builds on the episodic birth-death process, where speciation and extinction rates are constant within an interval but may shift instantly to new rates at a rate-shift episode [18][19][20][21] . Furthermore, we tested for a correlation between diversification rate and two environmental variables -atmospheric CO 2 concentration and average global paleo-temperature-using one existing [22][23][24][25][26][27] and three new environmentally-dependent diversification models.…”
Section: Introductionmentioning
confidence: 99%
“…tips (Wilberg et al 2019;Oaks 2011). To account for the possible effect of background rate variation, and for the possibility that a mass extinction is followed by a rapid burst of speciation (Crisp and Cook 2009), we employed time-varying priors on the speciation, extinction, and sampling rates through time (Magee et al 2020). We computed Bayes factors to test for the signal of a mass extinction event anytime along the phylogeny.…”
Section: K-pg Mass Extinction In Crocodylomorphamentioning
confidence: 99%
“…To account for background variation in the rates of speciation, extinction, and sampling, we apply horseshoe Markov random field (HSMRF) prior distributions (Magee et al 2020), which have been shown to be able to both detect rapid shifts in speciation rates and to reject time-varying models in favor of effectively constantrate models. In a HSMRF model, we must specify prior distributions on the initial rates λ 1 , µ 1 , and φ 1 .…”
Section: Priors and Parameterizationmentioning
confidence: 99%
See 1 more Smart Citation